Collective Knowledge and Skills of Planning and Executing Future-proof Curriculum Design of Outcomes-based Graduate Education - Eguia, Rec E. (Future Science / FSH-PH Publications, 2022)
The competitiveness of the workforce and the country's productivity in the future depend mainly on the quality of education. The strategic mindset of education leaders and planners, policymakers, administrators, researchers, teachers, students, and engagement of external stakeholders are some of the critical foundations of effective human capital development. Future-proof professionals are products of the quality of minds of the crafters and implementors of the graduate education curriculum. Therefore, education planners must be equipped with the necessary knowledge and skills of curriculum planning. The University of Southeastern Philippines, College of Development Management (USeP-CDM), explores the opportunity to create a global community of professionals by developing an Outcomes-based Graduate Education (OBGE). Thus, this study aimed to determine the collective knowledge and skills of planning and executing curriculum design of graduate education of the college. This study employed a qualitative method of research using action research. Action research is an appropriate design of the study because it is anchored on the principles of participation, empowerment and critical reflection in curriculum planning. Data were collected from the in-house faculty workshops and meetings, external stakeholders' consultations, and research conferences. Action learning and reflective practice were used to validate the predetermined themes of the collective knowledge and skills in the planning and executing curriculum design and development. The study revealed seven collective knowledge and skills demonstrated in planning and implementing the curriculum design and development. These knowledge and skills include Innovation, Design Thinking, Futures Literacy, Collaborative Foresight, Systems Thinking, Creative Thinking, and Reflective Practice. Finally, the study's findings showed that a newer sensibility of planning and execution of future-proof graduate education curriculum emanates from cultivating the knowledge creation process of the education planners, faculty, students, and administrators.